2015
DOI: 10.1039/c5cp01939g
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of retinal polyene (de)methylation on the photoisomerization mechanism and photon energy storage of rhodopsin

Abstract: Ab initio multiconfigurational quantum chemical methodology combined with molecular mechanics (CASPT2//CASSCF/AMBER) was applied to probe impacts of retinal protonated Schiff base (RPSB) polyene methylation and/or demethylation on the mechanism of photochemical isomerization in bovine rhodopsin. We have examined structural and spectroscopic properties of wild-type rhodopsin (with 11-cis-9,13-dimethyl-RPSB) and artificial rhodopsins, hosting four 11-cis-RPSB derivatives, 13-demethyl-, 9-demethyl-, 10-methyl-13-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 86 publications
(324 reference statements)
0
10
0
Order By: Relevance
“…Numerous computational investigations of absorption process in rhodopsin's chromophore involve geometry optimization at the DFT level of theory, as the DFT method seems to be more reliable to optimize the ground‐state geometry of RPSBs and RSBs than CASSCF method and much cheaper in terms of cpu time than MP2 method, followed by subsequent CASPT2 single‐point energy calculations . Therefore, there is a need to determine how the quality of the equilibrium geometry may affect the IPEA correction in the CASPT2 computational scheme.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous computational investigations of absorption process in rhodopsin's chromophore involve geometry optimization at the DFT level of theory, as the DFT method seems to be more reliable to optimize the ground‐state geometry of RPSBs and RSBs than CASSCF method and much cheaper in terms of cpu time than MP2 method, followed by subsequent CASPT2 single‐point energy calculations . Therefore, there is a need to determine how the quality of the equilibrium geometry may affect the IPEA correction in the CASPT2 computational scheme.…”
Section: Resultsmentioning
confidence: 99%
“…In the first case, most of the efforts of research were spent into the study of photochemical process in the bovine rhodopsin, which corresponds to the 11-cis to all-trans isomerization of the retinal protonated Schiff base. 88 Walczak and Andruniow 89 analyzed by using the CASPT2//CASSCF/MM hybrid approach the effects of retinal polyene (de)methylation on the photoisomerization mechanism. Garavelli and co-workers 90,91 showed the advantages of transient 2D electronic spectroscopy to track the evolution of the excited states of retinal along the photoisomerization path.…”
Section: E/z Photoisomerizationsmentioning
confidence: 99%
“…The photoisomerization of the retinal protonated Schiff base (RPSB) has been profusely studied from both a theoretical and an experimental point of view. Studies inside the protein ,, and in solution , have been performed in order to elucidate the role played by the protein in accelerating the cis/trans photoisomerization and increasing its quantum yield.…”
Section: Introductionmentioning
confidence: 99%
“…Additional information about the de-excitation dynamics can been obtained by introducing small structural modifications ,,,, in the RPSB. Recently, Kukura and co-workers , have shown that the addition of a methyl group at the C 10 position (see Figure ) of RPSB accelerates the electronic decay in methanol solution for both the cis and all- trans isomers and results in protein-like photophysics.…”
Section: Introductionmentioning
confidence: 99%